Electronic Patient Reported Outcome (ePRO) measures in patients with Soft Tissue Sarcoma (STS) receiving palliative treatment - Hofer, Silvia; Hentschel, Leopold; Richter, Stephan; Blum, Veronika; Kramer, Michael; Kasper, Bernd; Riese, Christoph; Schuler, Markus K. (Cancers, 2023)
The PazoQoL prospective, randomized, controlled, multicenter study was designed to continuously assess global health related quality of life (HRQoL) during treatment with pazopanib or physician-preferred chemotherapy over a 9-week period. The questionnaires were completed by the patients at home with great reliability during this time period. Continuous electronic patient reported outcome (ePRO) enabled early detection of the onset of deterioration and timely initiation of countermeasures. The Cancer Therapy Satisfaction Questionnaire (CTSQ) showed high interindividual variability and decline over a 9-week period, whereas the Time Trade-off (TTO) proved to be an efficient method for assessing individual benefit from cancer therapy. In our cohort, the TTO clearly demonstrated that the prolongation of life and the side effect profile of continued therapy were not as satisfactory as expected by patients when starting a new therapy. Although the study had to be stopped early due to the pandemic, our findings could translate into clinical practice without much effort and outside of a trial.